2012
DOI: 10.1111/j.1746-1561.2012.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Active Generations: An Intergenerational Approach to Preventing Childhood Obesity

Abstract: Active Generations is a promising childhood obesity prevention program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…However, vegetable intake increased marginally for the Energize group as compared to the control group over the 12 time points. Again, this finding is noteworthy given the small number of participants in this study and is similar to findings from another obesity intervention program study that found a 16% increase in vegetable consumption among 3rd‐ to 5th‐grade children . One explanation for this result could be the emphasis on trying new fruits and vegetables in class.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, vegetable intake increased marginally for the Energize group as compared to the control group over the 12 time points. Again, this finding is noteworthy given the small number of participants in this study and is similar to findings from another obesity intervention program study that found a 16% increase in vegetable consumption among 3rd‐ to 5th‐grade children . One explanation for this result could be the emphasis on trying new fruits and vegetables in class.…”
Section: Discussionsupporting
confidence: 86%
“…Again, this finding is noteworthy given the small number of participants in this study and is similar to findings from another obesity intervention program study that found a 16% increase in vegetable consumption among 3rd-to 5th-grade children. 21 One explanation for this result could be the emphasis on trying new fruits and vegetables in class. The children especially enjoyed trying edamame and radishes.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these children are also often making their own meals and snacks with limited parental monitoring and limited engagement in moderate‐to‐vigorous physical activity during the SS . Therefore, summer programs such as the VERB™ Summer Scorecard, BOUNCE, and Active Generations that provide opportunities in a safe place for children to participate in physical activities and practice good nutritional habits are needed to sustain healthy weight and aerobic fitness levels. Practically, such programs could evolve from local health councils in schools working to build relationships with community groups targeting summertime youth activity needs, opportunities, and resources.…”
Section: Discussionmentioning
confidence: 99%
“…One potential strategy for increasing physical activity in children from underserved communities is to develop intergenerational programs (Davison, Jurkowski, Li, Kranz, & Lawson, 2013; Flora & Faulkner, 2007; Swanson, Studts, Bardach, Bersamin, & Schoenberg, 2011; Werner, Teufel, Holtgrave, & Brown, 2012). Given that children's health habits develop within the context of a family, intergenerational interventions that include parents, grandparents, or other adult caregivers can be promising modalities for supporting health behaviors (Kuo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%